AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BAWANG PUTIH (Allium sativum) TERHADAP Mycobacterium tuberculosis DAN MULTIDRUG RESISTANT Mycobacterium tuberculosis AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BAWANG PUTIH (Allium sativum) TERHADAP Mycobacterium tuberculosis DAN MULTIDRUG RESISTANT Mycobacterium tuberculosis - , YANANTRI BINGA RAMSIF ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. This is primary global health problem and the second rank causing death among infectious disease in the world after human immunodeficiency virus (HIV). Other problem is MDR-TB, so the development for new drugs is needed. In Indonesia, there are so many herbal plants, one of them is garlic as antibacterial, but the clinical evidence of it, is rarely found. Objective: To know the antibacterial effect of ethanol extract frim garlic to Mycobacterium tuberculosis. Methods: Subjects are Mycobacterium tuberculosis strain H37RV and Multidrugs Resistance M. tuberculosis (MDR-TB). In this study, the bacteria are cultured in LJ medium which previously mixed with garlicâs extract in various concentrations. Results: Minimum Bactericidal Concentration of garlicâs extract for culture method is 2% to Mycobacterium tuberculosis strain H37RV and 4% to Multidrug Resistant Mycobacterium tuberculosis (MDR-TB). Conclusion: The ethanol extract from garlic has antibacterial effect to Mycobacterium tuberculosis strain H37RV dan Multidrug Resistant Mycobacterium tuberculosis (MDR-TB).